THEORETICAL BASIS OF USING HADITHS IN TEACHING THE SUBJECT OF "EDUCATION" (Universal International Scientific Journal, 2026)
This article aims to develop pedagogical tools and methods for using hadiths in teaching education in general secondary schools and to create and implement a modern methodology.
Keywords: methodology, hadiths, practice, standards, improvement, complex, development, personnel, dedication, spiritual maturity.